2015
DOI: 10.1002/pc.23757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of multi-walled carbon nanotubes on the thermomechanical properties of epoxy resin

Abstract: The influence of multi‐walled carbon nanotubes (MWCNTs) on thermosetting epoxy is examined using dynamic mechanical analysis, thermogravimetric analysis, and differential scanning calorimetry (DSC). Specimens are prepared with loadings of 0.1 and 1 wt% MWCNTs which are dispersed in the resin using two different dispersion methods. While the storage modulus of the specimens is improved, both the glass transition temperature and the thermal stability are reduced by the addition of MWCNTs with both effects being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Due to high thermal conductivity of the CNTs, there is further increase in heat diffusion, resulting in faster degradation of the polymer . Also, the lower crosslink density (as discussed in the Thermomechanical Analysis section) in epoxy due to CNT reinforcement contributes toward the reduced thermal stability …”
Section: Resultsmentioning
confidence: 99%
“…Due to high thermal conductivity of the CNTs, there is further increase in heat diffusion, resulting in faster degradation of the polymer . Also, the lower crosslink density (as discussed in the Thermomechanical Analysis section) in epoxy due to CNT reinforcement contributes toward the reduced thermal stability …”
Section: Resultsmentioning
confidence: 99%
“…Most authors have reported that the incorporation of carbon nanoparticles facilitates crosslinking (Figure ) by decreasing the heat of reaction ( ΔH r ) and the exothermic peak temperature, which has been ascribed to the high thermal conductivity of the CNTs and the ability of the epoxy resin to open the CNT bundles creating a higher surface for heat propagation. However, other authors have observed that the addition of CNTs hinders the crosslinking reaction between the epoxy and hardener, ascribed to a decrease of the fluidity of system ,. DSC results indicated that the level of residual unreacted epoxy increased gradually with the addition of CNTs, related to the formation of bundles and aggregates at high loading levels.…”
Section: Production Of Epoxy Nanocompositesmentioning
confidence: 86%
“…The glass transition temperature ( T g ) thus determined from the thermograms are reported in Figure B. Highest T g was observed for neat GE composite, that is, 105°C, but with the addition of CNT, T g decreased to 95°C . This reduction may be the result of the chemical restructuring of the matrix around pristine CNTs or in the interphase region, schematically represented in Figure .…”
Section: Resultsmentioning
confidence: 99%